Sintesis dan Aplikasi Karboksimetil Kitosan sebagai Inhibitor Korosi pada Baja Karbon dalam Air - Erna, Maria; Emriadi, Emriadi; Alif, Admin; Arief, Syukri; Noordin, Mohd Jain (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
Carboxymethyl chitosan (CMC) was synthesized with different methods by reacting chitosan with monochloroaceticacid in the presence of sodium hydroxide under variation conditions. The above samples were characterized byFourier transform infrared spectroscopy (FTIR) and soluble in water in range of pH. The CMc were soluble in watera wide range of pH and applied as corrosion inhibitor for steel in water. The inhibiting influence of CMC was studiedby potentiodynamic polarization method. It was found thad corrosion rate was dependent on water pH and CMCconcentration. The results show that optimum the inhibition efficiency at pH 5 and 1 ppm concentration CMC, i.e.,77%. The adsorption of used compound on the steel surface obeys modified Langmuir isotherm. Polarizationmeasurement show that the CMC acts essentially as a anodic-type inhibitor.